Predicting Psychological Well-Being Based on Psychological Capital Components and Stress Coping Strategies: A Case Study of Hormozgan Province Gas Company - Azadeh ASKARI; Bahman BAZGIR; Zahra KARIMIFARD; Maryam GHOLIPOUR; Bahareh ESLAMI; Najme SADEGHI (بهداشت کار و ارتقای سلامت, 2022)
Introduction: The increasing importance of having capable employees in organizations to achieve the goals emphasizes the need to pay more attention to the psychological well-being of employees and the factors affecting it. This study aims to investigate the role of components of psychological capital and stress coping strategies in predicting the psychological well-being of employees of Hormozgan Gas Company. Methods: This applied correlational study was conducted cross-sectionally and by cluster sampling method in 1400 on 130 personnel of Hormozgan Gas Company. In order to collect data, Lutans Psychological Capital Questionnaire (PCQ), Coping Inventory for Stressful Situations (CISS-21), and Reef Psychological Well-Being scale (RSPWB) were used. Then, the data were analyzed using SPSS-24 software and stepwise regression test. Results: The results of this study showed that there is a positive correlation between psychological well-being and psychological capital and problem-based coping strategies and a negative correlation between psychological well-being and emotion-centered coping strategy. The variables of hope, resilience, and emotion-based coping strategy have an effective predictive role on the psychological well-being index. Conclusion: High resilience and hope and the use of problem-oriented coping styles predict higher psychological well-being of employees. Therefore, it is suggested that managers consider more educational programs to improve psychological capital, educate appropriate coping styles, and use more problem-solving strategies for employees, and strengthen resilience and hope in them.